Neutron production in deuterium gas-puff z-pinch with outer plasma shell at current of 3 MA - Cikhardt J.; Klir D.; Rezac K.; Cikhardtova B.; Kravarik J.; Kubes P.; Sila O.; Cherdizov R. K. Rustam Koshalievich; Frusov F. I.; Kokshenev V. A. Vladimir Alekseevich; Kurmaev N. E. Nikolay Evgenjevich; Labetsky A. Yu. Aleksey Yurjevich; et al. (2015, 2015)
Title screen